PROTACs: The Future of Leukemia Therapeutics - Anwar, Zubair; Ali, Muhammad Shahzad; Galvano, Antonio; Perez, Alessandro; La Mantia, Maria; Bukhari, Ihtisham; Swiatczak, Bartlomiej (Frontiers in Cell and Developmental Biology, 2022)
The fight to find effective, long-lasting treatments for cancer has led many researchers to consider protein degrading entities. Recent developments in PROteolysis TArgeting Chimeras (PROTACs) have signified their potential as possible cancer therapies. PROTACs are small molecule, protein degraders that function by hijacking the built-in Ubiquitin-Proteasome pathway. This review mainly focuses on the general design and functioning of PROTACs as well as current advancements in the development of PROTACs as anticancer therapies. Particular emphasis is given to PROTACs designed against various types of Leukemia/Blood malignancies.